2014
DOI: 10.1093/bioinformatics/btu537
|View full text |Cite
|
Sign up to set email alerts
|

HapMuC: somatic mutation calling using heterozygous germ line variants near candidate mutations

Abstract: Motivation: Identifying somatic changes from tumor and matched normal sequences has become a standard approach in cancer research. More specifically, this requires accurate detection of somatic point mutations with low allele frequencies in impure and heterogeneous cancer samples. Although haplotype phasing information derived by using heterozygous germ line variants near candidate mutations would improve accuracy, no somatic mutation caller that uses such information is currently available.Results: We propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Haplotype-based strategy (as opposed to the mainstream position-based strategy) is widely adopted by structural variant callers in which reads need to be assembled to reconstruct long variants. It is also a powerful strategy for SNV detection and used by Platypus, HapMuC, LocHap, FreeBayes, and MuTect2 [35] , [41] , [42] , [43] , [44] . These algorithms locally assemble reads in a region and generate candidate haplotypes that may be represented by de Bruijn-like graphs.…”
Section: Matched Tumor-normal Variant Callingmentioning
confidence: 99%
“…Haplotype-based strategy (as opposed to the mainstream position-based strategy) is widely adopted by structural variant callers in which reads need to be assembled to reconstruct long variants. It is also a powerful strategy for SNV detection and used by Platypus, HapMuC, LocHap, FreeBayes, and MuTect2 [35] , [41] , [42] , [43] , [44] . These algorithms locally assemble reads in a region and generate candidate haplotypes that may be represented by de Bruijn-like graphs.…”
Section: Matched Tumor-normal Variant Callingmentioning
confidence: 99%
“…RAS proteins are small GTPases functioning as GDP-GTP-regulated binary switches that control many fundamental cellular processes. RAS proteins connect a great variety of upstream signals from activated Heuristic approaches qSNP [31] , RADIA [32] , Shimmer [33] , SOAPsnv [34] , VarDict [35] , VarScan2 [36] Joint genotype analysis CaVEMan [37] , FaSD-somatic [38] , JointSNVMix2 [39] , SAMtools [40] , Seurat* [41] , SNVSniffer [42] , SomaticSniper [43] , Virmid [44] Allele frequency deepSNV [45] , EBCall [46] , LoFreq [47] , LoLoPicker [48] , MuTect [49] , Strelka [50] Haplotype analysis FreeBayes [51] , HapMuC [52] , LocHap [53] , MuTect2 [49] , Platypus [54] Machine learning BAYSIC [55] , MutationSeq [56] , SNooPer [57] , SomaticSeq [58] Single-sample analysis GATKcan [59] , ISOWN [60] , OutLyzer [61] , Pisces [62] , SiNVICT [63] , SomVarIUS [64] Structural or copy number variation calling APOLOH [65] , BIC-Seq [66] , BreakDancer [67] , Break-Pointer [68] , CNVkit [69] , CoNIFER [70] , Delly [71] , HYDRA …”
Section: Rasmentioning
confidence: 99%
“…In this model, a paired-end read is assigned to a haplotype only if one of the ends overlaps a heterozygous variant phased by Long Ranger. Past work showed that even the phasing information from short fragments can improve mosaic variant calling accuracy [34]. We find while the precision is comparable to the Samovar full model, the number of variant calls is much lower, resulting in a genome-wide recall of 2.0% at 30X and 60X, because there are few sites for which adequate phasing information can be compiled from short reads alone ( Figure S4, Table S4).…”
Section: Simulation Experimentsmentioning
confidence: 73%
“…The mosaic mutation will likely be tolerated by the haplotype assembler and the reads will still be assigned to H2 ( Figure 1b). The fact that all the mosaic-carrying reads fall on the same haplotype is a hallmark of post-zygotic mosaicism [11] and contrasts with sequencing error, which would tend to distribute the "mosaic" alleles evenly across haplotypes [34]. Reads with the mosaic allele are called haplotype-discordant reads, and these are the most reliable kind of evidence we can gather in support of mosaic variants.…”
Section: Introductionmentioning
confidence: 99%